Diseño de una guía turística sobre la Ecorruta de Aviturismo ´Kuri Pishku, para difundir el turismo ecológico del cantón Patate - Imbago Rosero, Alison Nayeli (2025)
The objective of this project is to design a tourist guide on the Kuri Pishku Birdwatching Eco-route to promote ecological tourism in the Patate canton, given the lack of information resources that limits its correct dissemination, despite the biodiversity of the area. For the research, the deductive method was used, with a qualitative approach, in bibliographic and field mode, with an exploratory and descriptive level. To collect information, interviews were conducted with tourism professionals, local guides, biologists and graphic designers, as well as a focus group with people interested in birdwatching and with experience in the field to identify needs and expectations about the final proposal. As a result, solutions are given for the development of a tourist guide, where photography, illustration and narrative elements are involved as key pieces to promote this activity and make Patate known as an ecological destination. This project will serve as a basis for future projects related to the Kuri Pishku Birdwatching Ecoroute, recommending the collaboration of experts to ensure the quality of information.